Credit, Fiscal Policy, and Income Inequality: Empirical Study from Indonesia - Teguh Rochmat Maulidi; Taufiq C. Dawood; Miksalmina Miksalmina (Research Collaboration Community (RCC), 2022)
This paper investigates the relationship between credit, fiscal policy and income inequality in Indonesia. Annual data collected from Central Statistic Bureau is used from 2010 to 2020. The analytical method of this research is Genralized Least Square (GLS) to examine the relationship between variables. The results show that credit positively and significantly affects income inequality. Local government spending which is a proxy for fiscal policy has a significant and positive effect on income inequaity. The inflation variable has a significant positive effect on income inequality. However, the Gross Regional Domestic Product (GDRP) per capita has a significant negative effect on income inequality. Based on these findings, it is recommended that the government be able to maintain the momentum of the increasing trend of economic growth by providing the right stimulus, among others by providing access to credit that is easier to reach for the low-income class. In addition, local government expenditure allocations should be better allocated to provide benefits for increasing community income, such as social assistance in the form of direct assistance or free job training by utilizing job training centers tailored to each region's potential.